Outlander's tactile caress: a multisensory romance. Issue 5 (3rd September 2019) - Bellas, Athena
ABSTRACT: Much of the existing literature on Outlander emphasises its prioritisation of a female gaze. This is important to discussions of shifting representations of gender and sex in contemporary television. In this paper, however, I consider how the lush tactility of 'The Wedding' episode's sex scenes forms a potentially feminist sensuous aesthetic. Techniques like high contrast lighting, caressing gestures, extended shot duration, heavy use of extreme close-ups, slow panning camera-work, and a rich, warm colour palette, encourage a fleshy spectatorial encounter with the image. The purpose of this paper is to theorise this carnal dimension of engaging with Outlander .